Effects of planting patterns on physicochemical properties, metabolites and microbial community structure of rhizosphere soil in perennial cultivated grassland - Zhang, Xiaofang; Zhang, Chunping; Liu, Yuzhen; Huo, Lian; Yang, Zengzeng; Tong, Yongshang; Zhang, Xue; Yu, Zehang; Yang, Xiaoxia; Cao, Quan; Dong, Quanmin (Scientific reports, 2025)
Establishing perennial cultivated grasslands on the Qinghai-Tibet Plateau helps address the seasonal imbalance of forage resources and supports the restoration of degraded grasslands. The most common planting patterns—monocropping and mixed cropping—are well-studied in terms of vegetation structure, productivity, and soil nutrients. Despite their significance, the influence of prolonged planting practices on underground soil microbial communities and metabolites has often been neglected. In this study, two characteristic plants, Festuca sinensis ‘Qinghai’ and Poa pratensis ‘Qinghai’, from the area around Qinghai Lake were selected as the experimental subjects by employing 16 S and ITS sequencing methods in conjunction with non-targeted metabolomics analysis. The effects of planting patterns (monocropping and mixed cropping) on rhizosphere soil characteristics, metabolites and microbial community structure were examined. The results showed that compared with monocropping, mixed cropping significantly increased the contents of soil nutrients and key metabolites. In addition, it had a greater impact on fungal diversity than bacterial diversity, particularly in terms of β-diversity. While microbial α-diversity and dominant phyla remained stable, soil fungi were more responsive to changes in soil properties and metabolites. These results show that the new niche differentiation between different species in mixed grassland stimulates the secretion of trehalose and valine, which further affects the fungal community structure and enhances the soil nutrients and ecological functions of degraded grasslands. These findings will guide the restoration of degraded grasslands around Qinghai Lake and the selection of planting strategies to improve local sustainable grassland productivity.